EARLY LEARNING OF A FORIGN LANGUAGE - Bobokulova Shakhnoza Bakhriddinovna (Galaxy International Interdisciplinary Research Journal, 2023)
Recently, foreign languages have been the object of close attention and study not only by specialists and linguists, but also by ordinary people. At the same time, there is an ever-increasing role played by foreign languages in influencing the consciousness and activity of almost all segments of the population1. It is also necessary to note the fact that knowledge of foreign languages is very significant in the field of personal and professional communication of a person, which allows him to be one step ahead of others in the preferred plan for employers.